Characteristic biflavonoids from Daphne kiusiana var. atrocaulis (Rehd.) F. Maekawa. Issue 9 (3rd May 2023) - Bai, Zisong; Zhou, Di; Meng, Qingqi; Fang, Mingxia; Chen, Gang; Hou, Yue; Li, Ning
Abstract: Structurally diverse biflavonoids have attracted significant research interest for drug discovery over past decades. Biflavonoid oriented phytochemistry research on the stems of Daphne kiusiana var. atrocaulis (Rehd.) F. Maekawa was carried out, which resulted in the identification of ten major effective components (1 –10 ), including the undescribed biflavonoids, daphnodorin Q (1 ), daphnodorin R (2 ) and flavane, daphnekiuslin A (10 ). The known structures were identified from this herb for the first time. Their structures were determined by combination of multiple spectroscopic data as well as calculated electronic circular dichroism (ECD). All the identified compounds were evaluated for the anti-neuroinflammatory effects. Compound 9 could inhibit the overactivation of BV-2 cells induced by lipopolysaccharide with IC50 value at 26.32 μM. Graphical Abstract: UF0001